Analysis of a greenhouse thermal performance using dynamic simulations - Barragán-Medrano, Juan Carlos; Rodríguez Muñoz, Norma Alejandra; Najera-Trejo, Mario; Escobedo-Bretado, Jorge Alberto; Martin-Domínguez, Ignacio Ramiro; Venegas-Reyes, Eduardo; Ortega-Ávila, Naghelli (Acta Universitaria, 2019)
Four different shapes of a 182 m2 research greenhouse were analyzed using dynamic simulations. The thermal performance was evaluated using different cover materials at an equal floor area. In developing countries, the selection of the greenhouse shape, structure, and cover material generally is made based on the availability of the materials and considering the initial investment costs. The greenhouse is located on a cold semi-arid (BSk) climate according to the Köppen climate classification. This study aimed to determine the best choice of the greenhouse shape and cover material according to a technical-economic analysis. The analysis was conducted from a technical-economic perspective for this specific climate region. The results show the heating and cooling energy consumption for different cover materials and greenhouse shapes. The economic analysis was made to assess the investment and operative costs through the life span of the greenhouse.